Rodent Models of Invasive Aspergillosis due to Aspergillus fumigatus: Still a Long Path toward Standardization - Desoubeaux, Guillaume; Cray, Carolyn (Frontiers in Microbiology, 2017)
Invasive aspergillosis has been studied in laboratory by the means of plethora of distinct animal models. They were developed to address pathophysiology, therapy, diagnosis or miscellaneous other concerns associated. However, there are great discrepancies regarding all the experimental variables of animal models, and a thorough focus on them is needed. This systematic review completed a comprehensive bibliographic analysis specifically-based on the technical features of rodent models infected with Aspergillus fumigatus. Out the 800 articles reviewed, it was shown that mice remained the preferred model (85.8% of the referenced reports), above rats (10.8%) and guinea pigs (3.8%). Three quarters of the models involved immunocompromised status, mainly by steroids (44.4%) and/or alkylating drugs (42.9%), but only 27.7% were reported to receive antibiotic prophylaxis to prevent from bacterial infection. Injection of spores (30.0%) and inhalation/deposition into respiratory airways (66.9%) were the most used routes for experimental inoculation. Overall, more than 230 distinct A. fumigatus strains were used in models. Of all the published studies, 18.4% did not mention usage of any diagnostic tool, like histopathology or mycological culture, to control correct implementation of the disease and to measure outcome. In light of these findings, a consensus discussion should be engaged to establish a minimum standardization, although this may not be consistently suitable for addressing all the specific aspects of invasive aspergillosis.